Biological activity estimation of radiation metabolites of different organochlorinated pesticides - Melnikova, Tatiana V.; Polyakova, Lyudmila P.; Oudalova, Alla A. (Journal of the Belarusian State University. Ecology, 2018)
The study was aimed at determination of the potential danger of organochlorinated pesticides (OCP) radiolysis products under conditions when pesticides at very low concentrations, similar to their actual content in agricultural and food products, are exposed to γ-radiation. Data obtained at OCP radiolysis (α-HCH, γ-HCH, DDT and DDE) at irradiation of the pesticides model solutions with dose and dose rate usually applied for radiation processing of food were compared to findings from toxicity testing of postradiation products with bioassay. OCP molecules stability was determined at irradiation conditions studied. Chromatographic analysis showed that the OCP radiation-chemical yield was dependent on pesticides chemical nature and the polarity of the irradiated medium. Biological activity of OCP radiation metabolites was studied with infusoria spirosteomy (Spirostomum ambiguum) as a test-species. Spontaneous motor activity (SMA) of infusoria spirosteomy in media containing individual OCP before and after irradiation was estimated, according to a developed approach. Toxicity of OCP radiolysis products (remains of undegraded pesticides and their radiation metabolites) was assessed through an alteration of the SMA comparing to control value. It was found that the toxicity of the substances formed after irradiation was dependent on the pesticide degradation degree as well as on their chemical nature and the polarity of the irradiated medium.